Introduction to preschool: strategies for managing the gap between home and preschool. Issue 2 (4th May 2017) - Markström, Ann-Marie; Simonsson, Maria
ABSTRACT: The overall aim of this article is to investigate Swedish preschool teachers' perceptions of the interaction between home and institution in relation to children's introduction to preschool. The focus of this article is on their talk about how they manage the gap between home and preschool in the introduction process. A discourse analysis is carried out, based on focus group interviews with seven preschool teacher teams that have started to use a more parent-active approach during the introduction of children to preschool. The results show that a parent-active introduction positions and governs parents to take a more self-regulative role in preschool from the beginning. The construction of the parent-active introduction discourse/practice produces new subject positions for the parents (and teachers) and creates expectations of intensified parental involvement in this institutional practice. Furthermore, the results indicate that the parents' active introduction also changes the teachers' own role and their attitudes toward the parents. The boundary work between the home and preschool seems to consist of negotiations and of the construction of an intermediate domain between home and preschool that draws on discourses of responsibility, performativity and efficiency.